Cardiovascular chronobiology and chronopharmacology: importance of timing of dosing - Lemmer, Björn (Blood pressure monitoring in cardiovascular medicine and therapeutics, 2001)
Heart rate was among the earliest physiological functions reported not to be constant throughout the 24 h of a day (1). As early as at the beginning of the 17th century, daily variations in pulse rate, as well as a rapid increase on awakening, were described (2). In the 18th and 19th centuries, general observations as well as detailed data on daily variations in pulse rate and pulse quality were reported (3-11). The pulse of a healthy subject as determined in the late afternoon was even proposed as a easily available “metronom” to be used by musicians (12) (see Fig. 1). The metronom itself was not invented until 1816 by Mälzel.